2007
DOI: 10.1088/1742-6596/92/1/012139
|View full text |Cite
|
Sign up to set email alerts
|

Linearized force constants method for lattice dynamics in mixed semiconductors

Abstract: A simple and accurate method of calculating phonon spectra in mixed semiconductors alloys, on the basis of preliminarily (from first principles) relaxed atomic structure, is proposed and tested for (Zn,Be)Se and (Ga,In)As solid solutions. The method uses an observation that the interatomic force constants, calculated ab initio for a number of microscopic configurations in the systems cited, show a clear linear variation of the main (diagonal) values of the interatomic force constants with the corresponding bon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…First, some of us checked the falling down of interatomic force constants in semiconductor alloys with distance, and found that the interactions beyond the second neighbors can be safely discarded, without noticeable differences in the phonon spectra. 32 In our supercell with an impurity pair, none of the second neighbors of an impurity is simultaneously a second neighbor to a spurious (translated) impurity. Second, even with the break of symmetry introduced by an impurity pair, the relaxed shape of the supercell remains remarkably cubic.…”
Section: Ab Initio 'Protocol' For a Self-sufficient Percolation Modelmentioning
confidence: 98%
“…First, some of us checked the falling down of interatomic force constants in semiconductor alloys with distance, and found that the interactions beyond the second neighbors can be safely discarded, without noticeable differences in the phonon spectra. 32 In our supercell with an impurity pair, none of the second neighbors of an impurity is simultaneously a second neighbor to a spurious (translated) impurity. Second, even with the break of symmetry introduced by an impurity pair, the relaxed shape of the supercell remains remarkably cubic.…”
Section: Ab Initio 'Protocol' For a Self-sufficient Percolation Modelmentioning
confidence: 98%
“…Studies of vibrational properties therefore typically assume that the strength of the bonds and thus the frequency of the oscillations change proportionally to this change in bond lengths [21,22], a law commonly referred to as Grüneisen relation. Ab initio finitedisplacements calculations support the assumption of a linear relation between bond-stretching force constants and bond lengths for (In,Ga)As [23], but the proportionality factors differ substantially. Additionally, molecular dynamics simulations for (In,Ga)As [24] and first-principles calculations for (In,Ga)P [19] hint at a strong composition dependence of the force constants leading to a bond strength inversion.…”
Section: Introductionmentioning
confidence: 83%
“…Ab initio finite-displacements calculations in 64-atom (In,Ga)As supercells suggest that the influence of the matrix conserves the strict correlation between force constant k and bond length d [23]. The relation is linear with approximately the same slope for k Ga−As and k In−As , but it differs substantially from the empirical law for binary III-V materials [37].…”
Section: A Local Bond Picturementioning
confidence: 89%
See 1 more Smart Citation
“…First, some of us checked the falling down of interatomic force constants in semiconductor alloys with distance, and found that the interactions beyond the second neighbors can be safely discarded, without noticeable differences in the phonon spectra. 32 In our supercell with an impurity pair, none of the second neighbors of I: Comparison of the theoretical (ωimp, ∆) values of the leading AB1−xCx alloys in the MREI-VCA classification, as derived from the ab initio 'protocol', with the experimental ones. A more explicit notation for ωimp is AB:C (AC:B), that refers to an isolated B (C) atom in pure AC (AB).…”
Section: Ab Initio 'Protocol' For a Self-sufficient Percolation Modelmentioning
confidence: 99%